ANALISIS MAKNA KATA DAN GAYA BAHASA PADA IKLAN MINUMAN DI MEDIA ELEKTRONIK SERTA PEMANFAATANNYA PADA PEMBELAJARAN BAHASA INDONESIA DI SMA - Wilda Anggraeni Mila; Meliyawati; Yasser Arafat (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Advertising language combines informative and persuasive elements to influence audience perception and behavior. In milk beverage advertisements, language is used not only to present product information but also to create emotional appeal, build brand image, and stimulate consumer interest. This study aims to analyze the meanings of words and the use of figurative language in milk beverage advertisements in electronic media, as well as to explore their potential utilization in Indonesian language learning at the senior high school level. The research subjects include several milk beverage advertisements broadcast on television and online platforms. This study employs a qualitative descriptive method with a content analysis approach to identify and interpret linguistic features related to word meanings and stylistic expressions. The results show that the advertisements contain denotative, connotative, lexical, and grammatical meanings that emphasize both factual and emotional messages. In addition, four dominant types of figurative language—comparison, contrast, repetition, and association—are found to reinforce persuasion, increase memorability, and evoke emotional responses. The discussion highlights that these linguistic elements not only strengthen the persuasive effect of advertisements but also provide valuable material for contextual learning in the classroom. Therefore, the findings can be applied in teaching advertising texts and persuasive writing in Indonesian language learning. In conclusion, advertising language serves as both a communication strategy and an educational resource that enhances students’ critical and creative thinking in line with the principles of the Independent Curriculum.